Dampak Sosial Value Terhadap Trust Preseptor Mahasiswa Keperawatan - M. Arifki Zainaro; Usastiawaty Cik Ayu Saadiah Isnainy (Malahayati Nursing Journal, 2024)
ABSTRACT Trust can be formed through social values which provide a significant and measurable contribution to the effectiveness of student learning in carrying out their duties. The research aims to determine the influence of social values on trust—quantitative research method with SEM data analysis. The results of the social value research influenced -0.83. When receptors do not understand and cannot implement Social Value, it will hurt building Trust. This research contributes to developing human resources and developing student skills, maintaining and developing social values and trust in carrying out their professional duties. Preceptors to increase competency to improve preceptor performance. For higher education quality assurance management is planning and developing human resources for health workers, especially nursing preceptors. Keywords: Learning Effectiveness, Skills Improvement, Resource Development ABSTRAK Trust bisa terbentuk melalui social value yang memberikan kontribusi signifikan dan terukur terhadap efektivitas pembelajaran mahasiswa dalam menjalankan tugasnya. Tujuan penelitian unutk mengetahui pengaruh social value terhadap trust. Metode penelitian kuantitatif dengan analisis data SEM. Hasil penelitian social value berpenagruh sebesar -0,83. Ketika preseptor tidak paham dan tidak mampu mengimplementasikan Social Value, maka akan berdampak buruk terhadap terbangunnya Trust. Penelitian ini berkontribusi kepada pembinaan sumber daya manusia dan pengembangan keterampilan mahasiswa, menjaga dan menumbuh kembangkan nilai sosial dan trust dalam menjalankan tugas profesinya. Para preseptor dalam rangka meningkatkan kompetensi untuk meningkatkan kinerja preseptor. Untuk manajemen penjamin mutu Perguruan Tinggi sebagai perencanaan dan pengembangan SDM tenaga Kesehatan khususnya preseptor keperawatan. Kata Kunci: Efektivitas Pemebelajaran, Peningkatan Keterampilan,  Pembinaan                   Sumber Daya